The interest in disinterestedness: Lectures at the college de France (1987-1989) - Bourdieu, Pierre; Duval, Julien; Collier, Peter (Cambridge Polity press, 2024)
Is the state bureaucracy a universal class, as Hegel thought, or a structure that serves the interests of the dominant class, as Marx claimed? In his lecture courses at the Collège de France in 1987-88 and 1988-89, Pierre Bourdieu addressed these questions by examining the formation of the legal and bureaucratic fields characteristic of the modern state, uncovering the historical and social conditions that enable a social group to form and find its own interests in the very fact of serving interests that go beyond it.
Keywords: Political sociology; Sociology study and teaching (Higher) France; Interest philosophy